Algorithmic aspects of cloud computing : 5th International Symposium, ALGOCLOUD 2019, Munich, Germany, September 10, 2019, Revised Selected Papers /: 5th International Symposium, ALGOCLOUD 2019, Munich, Germany, September 10, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available